Implementasi Kebijakan Perencanaan Program Siaran Pro 2 RRI Sungailiat untuk Meningkatkan Minat dengar Generasi Muda di Kecamatan Sungailiat - Dewi Perwari (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to determine the implementation of RRI Sungailiat's Pro 2 broadcast program planning policy, which is directed at increasing the listening interest of the younger generation. First, a deep understanding of the younger generation's interests, preferences, and habits is necessary. Research on trends and interests of the younger generation helps in creating content that is relevant and interesting to them. Furthermore, innovation in event content and format is the key to attracting the younger generation's attention. Using podcasts, interactive segments, and audio-visual combinations provides listeners with a more engaging experience. Apart from that, utilizing digital platforms is an essential strategy. Radio must expand its presence on digital platforms used by the younger generation, such as social media, websites, and mobile applications. Radio can create a closer relationship with the younger generation by involving listeners through interaction and participation in programming. Collaboration with influencers, content creators, and online communities is also a practical step in attracting the younger generation's interest. Involving them in event programming or creating content can broaden the reach and increase the event's appeal. Continuous evaluation and improvement are essential to implementing broadcast program planning policies. Conclusion: By implementing broadcast program planning policies that include understanding the younger generation, content and format innovation, utilization of digital platforms, listener involvement, collaboration with influencers, and continuous evaluation, radio can attract the interest of younger listeners. Keywords: listening interest, policy, planning, pro two broadcast program, young generation